Entrepreneurs from low-skilled immigrant groups in knowledge-intensive industries - company characteristics, survival and innovative performance - Elisabeth Mueller (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2011)
This paper analyzes how companies of immigrant entrepreneurs in knowledgeintensive industries differ from companies of native entrepreneurs with respect to start-up characteristics, firm survival and innovative performance. I focus on immigrants from the 'recruitment countries' of south and southeast Europe, who arrived in Germany mainly in the 1970s to fill labor shortages. They are the largest immigrant group in Germany and can be reliably identified via ethnic name coding. Immigrant entrepreneurs are less than half as likely to found a company in a knowledge-intensive industry as native entrepreneurs. Firms owned exclusively by immigrants tend to be smaller and have higher exit rates. After controlling for resources, I found no differences in patenting activity compared to firms owned exclusively by natives. Firms in mixed immigrant/native ownership have no size disadvantage. In that group, exit rates are higher in services but not in manufacturing, and, again, there are no differences in patenting when resources are taken into account. The lower participation of immigrant entrepreneurs in knowledge-intensive industries can be explained by lower education levels, while smaller firm sizes suggest more limited access to capital.
urn:nbn:de:bsz:180-madoc-31818
Keywords: O32; O34; M13; J15; 330; immigrants; innovation; entrepreneurship; knowledge-intensive industries; Unternehmer; Migranten; Unternehmensgründung; Wissensintensives Unternehmen; Unternehmensentwicklung; Patent; Schätzung; Deutschland